2021
DOI: 10.1017/s1047951121000159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic exercise changes in venous pressure and liver stiffness in Fontan patients: effects of Treprostinil

Abstract: Background: Systemic venous hypertension and low cardiac output are believed to be important mediators of liver injury after the Fontan procedure. Pulmonary vasodilators have the potential to improve such haemodynamics. The aim of this study was to assess the acute effects of exercise on liver stiffness and venous pressures and to assess the impact of inhaled Treprostinil on this response. Methods: In this prospective, double-blind, placebo-controlled, crossover trial, 14 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, Egbe et al 19 demonstrated that diminished pulmonary vascular reserve correlates strongly with liver congestion and liver stiffness. 20,21 This diminished pulmonary vascular reserve was highly correlated with invasive central venous pressures and suggests that high venous pressure is indeed an important mechanism by which congestion and liver stiffness is mediated. In the present dataset, although not demonstrated directly, patients with the biggest livers likely reflect those with the greatest degree of liver congestion and systemic venous hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Egbe et al 19 demonstrated that diminished pulmonary vascular reserve correlates strongly with liver congestion and liver stiffness. 20,21 This diminished pulmonary vascular reserve was highly correlated with invasive central venous pressures and suggests that high venous pressure is indeed an important mechanism by which congestion and liver stiffness is mediated. In the present dataset, although not demonstrated directly, patients with the biggest livers likely reflect those with the greatest degree of liver congestion and systemic venous hypertension.…”
Section: Discussionmentioning
confidence: 97%